A day in memory of Claudio Chiuderi - Del Zanna, Luca; Bacciotti, Francesca (Il Colle di Galileo, 2023)
Claudio Chiuderi sadly passed away on the 30th of June 2022. A few months later in Arcetri friends and colleagues honoured his memory in an event described in this contribution. Claudio was the father of Italian research into astrophysical plasmas and, for many ex-students, simply THE professor, a mentor, a colleague and a friend.